Tribological behavior of Ti-5Al-2.5Sn, Ti-10v-2Fe-3Al and Ti-38al carburized via current heating technique with graphite powders - Boonruang C. (Japan Institute of Metals (JIM), 2014)
Tribological behavior of Ti-5Al-2.5Sn, Ti-10V-2Fe-3Al and Ti-38Al carburized via current heating technique with graphite powders was studied. In carburizing, the direct current was applied across the graphite powders and alloys with a fixed electric power from 120 to 180W for 20 min in argon atmosphere. The alloys were characterized using XRD, SEM, and hardness tester. Tribological behavior of the alloys was examined by pin-on-disk tribological test. Formation of TiC, TiC with VC and Ti2AlC with TiC on Ti-5Al-2.5Sn, Ti-10V-2Fe-3Al and Ti-38Al, respectively, could improve surface hardness and reduce friction coefficient leading to improve wear resistance of the alloys. Coatings of TiC totally exhibited higher wear resistance than that of Ti2AlC. Improvement of wear resistance was influenced by quality of coatings which could be sorted in descending as TiC, TiC with VC and Ti2AlC with TiC in the carburized Ti-5Al-2.5Sn, Ti-10V-2Fe-3Al and Ti-38Al, respectively. © 2014 The Japanese Society for Non-Destructive Inspection.